2005
DOI: 10.2337/diacare.28.5.1118
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Diabetes in the Absence of Nephropathy

Abstract: OBJECTIVE -Patients with diabetes commonly have a greater degree of anemia for their level of renal impairment than those presenting with other causes of renal failure. To clarify the contribution and differing roles of diabetes and nephropathy in the development of anemia in diabetic patients, we examined the hematologic and hematinic parameters of diabetic patients without nephropathy.RESEARCH DESIGN AND METHODS -The study group was comprised of 62 patients with type 2 diabetes who had been followed for a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 19 publications
11
75
1
6
Order By: Relevance
“…The present study therefore extends these findings to diabetic patients with modest renal impairment and normoand microalbuminuria. In diabetes, anaemia, associated with erythropoietin deficiency, appears to occur earlier in the course of progression of kidney disease than in non-diabetic patients with kidney diseases [2][3][4][5][6][7]. Haemoglobin concentrations were found to be significantly decreased in patients with microalbuminuria compared to patients with normoalbuminuria [3].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The present study therefore extends these findings to diabetic patients with modest renal impairment and normoand microalbuminuria. In diabetes, anaemia, associated with erythropoietin deficiency, appears to occur earlier in the course of progression of kidney disease than in non-diabetic patients with kidney diseases [2][3][4][5][6][7]. Haemoglobin concentrations were found to be significantly decreased in patients with microalbuminuria compared to patients with normoalbuminuria [3].…”
Section: Discussionmentioning
confidence: 93%
“…However, the precise mechanisms of anaemia in diabetic patients are unknown, and a decline in haemoglobin concentrations appears to occur earlier in diabetic patients with nephropathy than in patients with non-diabetic kidney diseases [2][3][4][5][6][7]. In addition to erythropoietin deficiency due to tubulointerstitial changes, which is an early morphological alteration of diabetic nephropathy [8], autonomic neuropathy [9,10] and increased serum advanced glycation end-products [11] may participate in the pathogenesis of anaemia in diabetic kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…2), an early marker of microvascular inflammation and damage [14], which, like anaemia [3], precedes declining renal function associated with late-stage nephropathy. Recently, it has also been shown that, even in the absence of albuminuria, anaemia in patients with diabetes is largely the result of impaired renal functioning [15]. These strong links between the kidney and anaemia in diabetes probably reflect the unique vulnerability of the renal microcirculation to damage in diabetes [16].…”
Section: Which Patients Will Have Anaemia?mentioning
confidence: 99%
“…One major factor in the genesis of anaemia is the failure to increase circulating erythropoietin concentrations in response to falling Hb (so-called functional erythropoietin deficiency) [4,15,18,19]. In healthy individuals, any decrease in Hb is normally matched by an exponential increase in renal erythropoietin production.…”
Section: Which Patients Will Have Anaemia?mentioning
confidence: 99%
“…The relationship between anaemia, diabetes and renal impairment has also been investigated in several small studies [10][11][12]. The Kidney Early Evaluation Study also reported diabetes to be independently correlated with anaemia in persons with moderate reduction in kidney function [13].…”
Section: Discussionmentioning
confidence: 99%